Spatial patterns of stable isotopes and trophic ecology in a hydropeaking river. (15th March 2022) - Jones, Nicholas E.; Haxton, Tim J.
Abstract: While the impacts of dams are known, there are gaps in our understanding, particularly with respect to longitudinal patterns of environmental and biological gradients downstream of dams. We investigated longitudinal patterns of stable isotope ratios of carbon and nitrogen in brook trout ( Salvelinus fontinalis ) in the regulated Magpie River. We also examined the diet of brook trout via mixing models using the dominant forage items in the river. For brook trout, δ 13 C values increased and δ 15 N values decreased in reaches progressing downstream. River distance downstream of the dam explained the variation in levels of stable isotopes in brook trout. Most changes occurred within the first eight kilometres of the river. The fish length had a significant but weak positive effect on stable isotope levels. Based on the MixSiar mixing model, the diet of brook trout consisted of 72% longnose dace, 27% benthic invertebrates, and 1% sculpin. The Magpie River had isotope values that were lower for δ 13 C and higher for δ 15 N when compared to nine neighbouring natural unregulated rivers. Previous research on the Magpie River demonstrated that the upstream reservoir exports large quantities of plankton that likely provides a quality food source for river biota and shows a clear downstream gradient in energy sources similar to the changes found for δ 13 C. For the Magpie River, and other regulated rivers, statistical comparisons of many abiotic and biotic variables, including stable isotopes, could lead to erroneous conclusions if samples are not collected with explicit consideration of spatial gradients.